Stereochemistry of Transition Metal Complexes Controlled by the Metallo-Anomeric Effect - Zhu, Feng; Walczak, Maciej A (Journal of the American Chemical Society, 2020)
The use of stereoelectronic interactions to control reactivity and selectivity has a long history in chemistry. The anomeric effect, one of the fundamental concepts in organic chemistry, describes the preferences of a substituent at the anomeric carbon in glycosides to adopt axial configuration when the anomeric group is an electronegative element such as oxygen or a halogen. The origin of the anomeric effect has been the subject of intense debate. Explanations capitalizing on either the delocalization of the endocyclic oxygen lone pair into the antibonding σ*(C–X) orbital or the minimization of the dipole–dipole interactions are currently the two leading theoretical models. Although the majority of experimental and theoretical studies have focused on the elements from groups 6 and 7, little is known about conformational preferences of tetrahydropyran rings substituted with a transition metal at the anomeric carbon and the role of these interactions in stereoselective synthesis. Here, we report studies on conformational and configurational preferences of organometallic complexes stabilized by vicinal heteroatoms. We provide computational evidence that late transition metals adopt the axial position in heterocycles or synclinal geometry in acyclic systems. Furthermore, the anomeric preferences of late transition metals correlate with the oxidation state of the metal and can be explained by hyperconjugative interactions between endocyclic heteroatom and the σ* acceptor orbitals of the C–M bond. In a broader context, this discovery provides insight into the role of previously unanticipated stereoelectronic effects that can be harnessed in the design of stereoselective reactions, including chemical glycosylation and enantioselective catalysis.